2018
DOI: 10.1111/1540-6229.12258
|View full text |Cite
|
Sign up to set email alerts
|

Riskiness of Real Estate Development: A Perspective from Urban Economics and Option Value Theory

Abstract: In this article, we define a new construct for urban economic and investment analysis, which revisits the conventional wisdom that investment in real estate development is riskier than investment in stabilized property assets. This new construct, referred as a "development asset value index" (DAVI), is a value index for newly developed properties (only) in a given geographical property market. It tracks longitudinal changes in the highest and best use (HBU) value of locations, and it reveals developer and land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Vacant land has the highest option value and capital requirements as there is no structure (e.g., see Cunningham, 2006; Titman, 1985). The land value fraction (land valuetotal property value$\frac{\text{land value}}{\text{total property value}}$) is 100%, whereas the average land value fraction for newly build properties is estimated to be 20% of total value (Albouy et al., 2018; Bokhari & Geltner, 2018; Geltner et al., 2020). Therefore, we assume buyers of vacant land deploy approximately 400% of the purchasing price in additional capital, far beyond the OZ program threshold of 100%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Vacant land has the highest option value and capital requirements as there is no structure (e.g., see Cunningham, 2006; Titman, 1985). The land value fraction (land valuetotal property value$\frac{\text{land value}}{\text{total property value}}$) is 100%, whereas the average land value fraction for newly build properties is estimated to be 20% of total value (Albouy et al., 2018; Bokhari & Geltner, 2018; Geltner et al., 2020). Therefore, we assume buyers of vacant land deploy approximately 400% of the purchasing price in additional capital, far beyond the OZ program threshold of 100%.…”
Section: Methodsmentioning
confidence: 99%
“…If a property is newly constructed, it will be built according to its HBU. It will have the optimal density (measured by floor area ratio [FAR]), and “best” property type to maximize NPV (see, e.g., Geltner et al., 2020). However, HBU can change over time, leading to “better” suited building types for a location.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Evans (2018), it is particularly very important in improving public health; reducing societal injustice and poverty; ensuring social order and accommodating population growth. According to Ezeh (2014), and (Geltner, 2018), several studies have indicated that public housing provision involves policy formulation, institutional development, actual housing provision, allocation and management. This goes to suggest that challenges in public housing provision are related to policy formulation, institutional growth and development as well as actual production and consumption of housing units and services (World Health Organization, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%